DEVELOPMENT PROSPECTS OF THE VEGETABLE FARMING SECTOR IN THE REPUBLIC OF UZBEKISTAN - Sobir Xasanov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
In recent years, systematic measures have been implemented in the Republic of Uzbekistan to reform the vegetable farming sector, introduce resource-saving technologies, and provide agricultural producers with modern machinery. As a result, by 2030, it is planned to increase the annual growth rate of value added in agriculture to 5%, expand agricultural and food exports to 20 billion US dollars, and raise labor productivity in agriculture per worker from the current USD 3,960 to USD 6,500 per year. This article substantiates the priority directions for the sustainable development of the vegetable farming sector under conditions of a free market economy, based on the example of enterprises with various forms of management. It highlights the economic significance of modern intensive methods in the development of vegetable production and examines the mechanisms for applying state economic incentives in the development of the sector. Additionally, recommendations are proposed for further development through the expansion of cooperative relations, and forecast indicators for the gross output value of the vegetable sector up to 2030 are developed.